2020
DOI: 10.1021/acs.joc.0c02412
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Nitroxyl (HNO) with Hydrogen Sulfide and Hydropersulfides

Abstract: Nitroxyl (HNO) has gained a considerable amount of attention because of its promising pharmacological effects. The biochemical mechanisms of HNO activity are associated with the modification of regulatory thiol proteins. Recently, several studies have suggested that hydropersulfides (RSSH), presumed signaling products of hydrogen sulfide (H 2 S)-mediated thiol (RSH) modification, are additional potential targets of HNO. However, the interaction of HNO with reactive sulfur species beyond thiols remains relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…[9] Recently Toscano et al reported the first characterization of HNO/H 2 S interaction, indicating stoichiometry-dependent production of sulfane sulfurs -hydrogen polysulfides (H 2 S n ) or sulfur (S 8 ). [10] We wondered if the dual donors could also produce sulfane sulfurs. 3 b was incubated with a sulfane sulfur sensitive fluorescent probe, SSP4, [11] for 24 hours at 37 °C.…”
Section: Chembiochemmentioning
confidence: 99%
“…[9] Recently Toscano et al reported the first characterization of HNO/H 2 S interaction, indicating stoichiometry-dependent production of sulfane sulfurs -hydrogen polysulfides (H 2 S n ) or sulfur (S 8 ). [10] We wondered if the dual donors could also produce sulfane sulfurs. 3 b was incubated with a sulfane sulfur sensitive fluorescent probe, SSP4, [11] for 24 hours at 37 °C.…”
Section: Chembiochemmentioning
confidence: 99%
“…The stoichiometric analyses of such reaction should also take into account the possibility of the reaction between HNO and released NH 2 OH ( Reaction 23 ). The recent study of Zarenkiewicz et al (2021) on HNO reaction with H 2 S shows that this reaction leads to the formation of hydrogen polysulfides (H 2 S n ) or sulfur S 8 , depending on the relative concentrations of H 2 S and HNO. The reactivity of HNO towards selected inorganic scavengers is summarized in Scheme 2 and Table 1 .…”
Section: Hno Chemistrymentioning
confidence: 99%
“…As hydropersulfides have been detected in biological systems at high micromolar concentrations, they could be among important biological targets of azanone. The recent study of Zarenkiewicz et al (2021) on HNO reaction with hydropersulfides shows that RSSH are more potent traps for HNO, than RSH. They also reported that HNO reaction with small molecule RSSH leads to the formation of various RSS n SR and RSS-NH-S n R species ( Zarenkiewicz et al, 2021 ).…”
Section: Hno Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to dimerization, HNO reacts with thiols, generating a N-hydroxysulfenamide intermediate that can rearrange to a sulfinamide or further react with more thiol to yield a disulfide and hydroxylamine [10]. HNO similarly reacts with hydrogen sulfide (H 2 S), a second recognized gasotransmitter [1], to give short-chain hydrogen polysulfides (H 2 S n ) or S 8 depending on the relative concentrations of HNO and H 2 S [11]. Based on this chemistry, HNO can influence thiol-mediated biochemistry and potentially H 2 S-controlled reactions.…”
Section: Introductionmentioning
confidence: 99%